2006
DOI: 10.1055/s-2006-954841
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Five Years Experience with Extracorporeal Septoplasty

Abstract: Even today, the difficult septum presents a surgical problem. A severe septum deformity is caused mostly by an accident or is seen in patients with malformations such as cleft lip and palate deformity. It is characterized by a massive malformation in all levels with consecutive blocking of one or both airways. Such marked septal deformities cannot be corrected properly by standard septoplasty techniques. Therefore, in such cases we suggest an extracorporeal septoplasty, where we take out the whole septum and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 13 publications
0
55
1
Order By: Relevance
“…The largest published retrospective study 9 to date of revision septoplasty cases (2168 patients in Scotland) found a similar revision rate between 3.2% and 4.4%. Other studies 10,11 show a slightly higher revision rate between 5% and 8% but again are limited in sample size and follow-up and were conducted at single institutions. Patients undergoing more complex surgical procedures such as cleft septorhinoplasty had a significantly higher revision rate of 16.9%.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The largest published retrospective study 9 to date of revision septoplasty cases (2168 patients in Scotland) found a similar revision rate between 3.2% and 4.4%. Other studies 10,11 show a slightly higher revision rate between 5% and 8% but again are limited in sample size and follow-up and were conducted at single institutions. Patients undergoing more complex surgical procedures such as cleft septorhinoplasty had a significantly higher revision rate of 16.9%.…”
Section: Discussionmentioning
confidence: 87%
“…In the literature focusing on specific rhinoplasty techniques, the revision rate varied from 4% to 15.5%. 3,4,7,8 In the septoplasty literature, a large study 9 of 2168 septoplasties by any technique showed a revision rate of 3.2% among experienced surgeons, while studies 10,11 focusing on specific septoplasty techniques showed higher revision rates of 7% to 8%. 911 In addition, there may be an underestimation of the revision rates reported in the literature because the authors of single-surgeon or single-institution studies 111 review their own respective data and do not include patients who seek revision surgery at another institution, thereby lowering the reported revision rates.…”
mentioning
confidence: 99%
“…These can be generally categorized into 2 types: in situ septoplasty techniques (including septal repositioning, 27 scoring and morselization, 28 suture techniques, 29 and septal batten graft) 30,31 and extracorporeal septoplasty techniques. 32,33 Generally, in situ septoplasty is reserved for less severe caudal deviations, whereas extracorporeal septoplasty is used in severe deviations or in deviations that persist after in situ techniques. Supporting this notion, Lee and Jang 34 performed a retrospective review comparing these 2 techniques in 169 subjects with caudal septal deviation and found that, although both could be performed with similar aesthetic outcomes, subjects who underwent extracorporeal septoplasty achieved superior functional results and were less likely to suffer from persistent or unresolved nasal obstruction (level 3 evidence).…”
Section: Septummentioning
confidence: 99%
“…Alternatively, a polydioxanone, PDS Flexible Plate (Ethicon, Inc., Somerville, NJ) may be used to augment reconstructed septum 18,20 (Fig. 3).…”
Section: Extracorporeal Septoplastymentioning
confidence: 99%